2010
DOI: 10.1007/s00438-010-0514-y
|View full text |Cite
|
Sign up to set email alerts
|

Gain of deleterious function causes an autoimmune response and Bateson–Dobzhansky–Muller incompatibility in rice

Abstract: Reproductive isolation plays an important role in speciation as it restricts gene flow and accelerates genetic divergence between formerly interbreeding population. In rice, hybrid breakdown is a common reproductive isolation observed in both intra and inter-specific crosses. It is a type of post-zygotic reproductive isolation in which sterility and weakness are manifested in the F(2) and later generations. In this study, the physiological and molecular basis of hybrid breakdown caused by two recessive genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 46 publications
2
116
1
Order By: Relevance
“…On the other hand, it was recently shown that a hybrid lethality allele has risen to high frequency in a population of M. guttatus due to linked selection for an allele that confers copper tolerance (Wright et al 2013). Natural selection is also presumed to play a role in divergence among disease resistance genes that cause hybrid necrosis in Arabidopsis and rice (Kruger et al 2002;Alcazar et al 2009;Jeuken et al 2009;Yamamoto et al 2010;Chen et al 2014), although direct population genetic evidence is lacking. Likewise, the genes that cause cytoplasmic male sterility between Mimulus species (involving the same IM62 and SF lines used in this study) seem more likely to have evolved by selfish mitochondrial evolution and compensatory nuclear coevolution than by genetic drift (Barr and Fishman 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it was recently shown that a hybrid lethality allele has risen to high frequency in a population of M. guttatus due to linked selection for an allele that confers copper tolerance (Wright et al 2013). Natural selection is also presumed to play a role in divergence among disease resistance genes that cause hybrid necrosis in Arabidopsis and rice (Kruger et al 2002;Alcazar et al 2009;Jeuken et al 2009;Yamamoto et al 2010;Chen et al 2014), although direct population genetic evidence is lacking. Likewise, the genes that cause cytoplasmic male sterility between Mimulus species (involving the same IM62 and SF lines used in this study) seem more likely to have evolved by selfish mitochondrial evolution and compensatory nuclear coevolution than by genetic drift (Barr and Fishman 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There are also hints that natural selection can contribute to the spread of incompatible alleles within populations and species. For example, plant hybrid necrosis has been mapped repeatedly to disease resistance genes (Krüger et al 2002; Alcazar et al 2009;Jeuken et al 2009;Yamamoto et al 2010;Chen et al 2014), which are likely targets of adaptive divergence to unique pathogen communities (Bomblies and Weigel 2007). Additionally, many hybrid incompatibility genes show molecular signatures of positive selection (Presgraves et al 2003;Brideau et al 2006;Maheshwari et al 2008;Oliver et al 2009;Phadnis and Orr 2009;Tang and Presgraves 2009), but, interestingly, few of these genes seem to be involved in classical ecological adaptation.…”
mentioning
confidence: 99%
“…Alcázar et al (2009) fine mapped a causal gene of incompatibility or hybrid breakdown to a cluster of TIR-NB-LRR genes in Arabidopsis. Yamamoto et al (2010) reported that hbd3, a causal gene controlling hybrid breakdown in rice, is located on the cluster of NB-LRR genes. These reports suggest that plant immune systems conditioned by NB-LRR protein(s) induce hybrid weakness, as reported by Bomblies and Weigel (2007).…”
Section: T14×(t65×ptb7)]mentioning
confidence: 99%
“…The molecular basis of hybrid incompatibility has been variously attributed to cisor trans-regulatory changes, copy number changes, and amino acid changes (Krüger et al, 2002;Bomblies et al, 2007;Dilkes et al, 2008;, and, thus far, there is little overlap between genes detected in one genus to another (reviewed in Rieseberg and Blackman, 2010). These interactions can affect different targets including pathogen responses (Bomblies et al, 2007;Jeuken et al, 2009;Yamamoto et al, 2010;Mizuno et al, 2011), suppression of transposable elements (TEs) (McClintock, 1984;Shaked et al, 2001;Kashkush et al, 2003;Madlung et al, 2005;Josefsson et al, 2006;Ungerer et al, 2006;Martienssen, 2010), small RNA pathways (Ha et al, 2009;Ng et al, 2012;Shivaprasad et al, 2012;Zhang et al, 2012), and developmental regulatory pathways, such as genomic imprinting in the seed (Josefsson et al, 2006). Importantly, although all these molecular mechanisms have been documented as affected by hybridization in at least one system, their relative contribution to hybrid incompatibility is unclear.…”
Section: Introductionmentioning
confidence: 99%